The potential of physic nut (Jatropha curcas Linn.) hybrid plant as a source of biodiesel at different planting location for dry land utilization. (February 2020) - Maftuchah,; Zainudin, Agus; Ikhwan, Ali; Winaya, Aris; Purnama, Adi; Sudarmo, Hadi
Abstract: Physic nut ( Jatropha curcas Linn.) is the one of prospective plants to be developed as biodiesel source in the tropical region. Hence, it is very important to expand the cultivation area of this plant. The purpose of this research was examined the crossed results of four genotypes of physic nut plant that potential to be developed as the promising genotypes for dry land area, namely JCUMM-5, JCUMM-6, JCUMM-7, and JCUMM18. The potential production of the four genotypes plant of J. curcas were selected for five years planting at two different locations which represent the dry land area, i.e., Pasuruan Regency of East Java, and North Lombok Regency of West Nusa Tenggara, Indonesia. The observations on the number of fruit bunches, fruits number, seeds dry weight, 100 seeds dry weight and seed oil content showed that JCUMM5, JCUMM7, and JCUMM18 were not significantly different ( P > 0 . 05 ) and the seeds production in kilogram of dry weight/ha/year higher than IP3A and IP3P as a control genotypes. Whereas the JCUMM18 genotype was the highest average on seeds dry weight (328.5 kg/ha/year) and North Lombok, West Nusa Tenggara location was higher on a number of fruit bunches, fruits number and 100 seeds dry weight than those in Pasuruan, East Java. However, the seed oil content from North Lombok was lower than in Pasuruan location.